Sixth-Grade Students’ Behavior Toward School Discipline: A Case Study from an Educational Management Perspective - Nur Agus Salim; Annisa Qomariah; Cindy Dyah Prihatiningsih (Journal of Educational Management Research, 2026)
This study aims to describe sixth-grade students’ behavior toward school discipline and to identify factors influencing disciplinary behavior from an educational management perspective. A qualitative approach with a case study design was employed. Data were collected through classroom observations, semi-structured interviews, and document analysis involving sixth-grade students, classroom teachers, and the school principal. The findings reveal that students’ disciplinary behavior can be classified into three levels: high, moderate, and low. While some students demonstrate consistent discipline, such as punctual attendance and compliance with school regulations, others exhibit indiscipline, including tardiness and neglect of cleanliness rules. Factors influencing disciplinary behavior include self-awareness, motivation, mindset, peer influence, family environment, and the effectiveness of school management practices, particularly leadership, rule enforcement, and school culture. The study implies that fostering student discipline cannot rely solely on punitive sanctions but requires systematic educational management strategies, including positive habituation, role modeling by teachers and school leaders, and collaborative partnerships between schools and parents. Strengthening managerial planning and supervision is essential to support sustainable disciplinary development in elementary education.